2010
DOI: 10.1105/tpc.110.078253
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin Regulates Compound Leaf Development in Tomato  

Abstract: Leaf shape diversity relies on transient morphogenetic activity in leaf margins. However, how this morphogenetic capacity is maintained is still poorly understood. Here, we uncover a role for the hormone cytokinin (CK) in the regulation of morphogenetic activity of compound leaves in tomato (Solanum lycopersicum). Manipulation of CK levels led to alterations in leaf complexity and revealed a unique potential for prolonged growth and morphogenesis in tomato leaves. We further demonstrate that the effect of CK o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
220
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(230 citation statements)
references
References 86 publications
4
220
3
3
Order By: Relevance
“…S3), indicating that lanolin paste treatment had only local effects within a leaf, although phyllotaxis can be altered. Consistently, adaxial IAA treatment was able to induce a shift of auxin signaling, indicated by the synthetic pDR5::3×Venus-N7 reporter (27), to the adaxial domain in tomato ( Fig. S4 A and B).…”
Section: Resultsmentioning
confidence: 51%
“…S3), indicating that lanolin paste treatment had only local effects within a leaf, although phyllotaxis can be altered. Consistently, adaxial IAA treatment was able to induce a shift of auxin signaling, indicated by the synthetic pDR5::3×Venus-N7 reporter (27), to the adaxial domain in tomato ( Fig. S4 A and B).…”
Section: Resultsmentioning
confidence: 51%
“…Thus, part of the difference between the simple Arabidopsis and the compound tomato leaf appears to stem from events that take place at the very first stages of leaf development. Tomato also differs from Arabidopsis in its sensitivity to miR319 activity during late stages of leaf development (Efroni et al, 2008), in agreement with the late expression of LA and the maintenance of morphogenetic capacity until very late stages of tomato leaf development (Shani et al, 2010) (this study). Our results suggest a dual role for LA-like proteins in developing tomato leaves: promoting the transition from PM to SM and keeping the morphogenetic activity of the leaf margin in check throughout development.…”
Section: Variations In Leaf Growth and Maturation Among Speciesmentioning
confidence: 70%
“…4). Interestingly, GA and cytokinin were both shown to modulate this late morphogenetic activity in tomato (Shani et al, 2010;Yanai et al, 2011). Cumulatively, these studies suggest that the flexibility of leaf shape is achieved by tuning the balance between hormones that promote indeterminate state, such as cytokinin, and hormones that promote differentiation, such as GA.…”
Section: Hormones Affecting the Balance Between Morphogenesis And Difmentioning
confidence: 95%
“…Interestingly, lettuce (Lactuca sativa) leaves that overexpress the Arabidopsis KNOXI gene BP acquire characteristics of indeterminate growth, which is associated with the accumulation of specific types of cytokinins (Frugis et al, 2001). Cytokinin was also shown to be involved in the maintenance of prolonged morphogenetic activity in the tomato leaf margin (Shani et al, 2010). Genetic and molecular analysis indicated that cytokinin acts downstream of KNOXI activity in delaying leaf maturation.…”
Section: Hormones Affecting the Balance Between Morphogenesis And Difmentioning
confidence: 99%